2020
DOI: 10.1002/ijc.33279
|View full text |Cite
|
Sign up to set email alerts
|

Treatment abandonment in children with cancer: Does a sex difference exist? A systematic review and meta‐analysis of evidence from low‐ and middle‐income countries

Abstract: In this systematic review and meta-analyses, we sought to determine sex-disparities in treatment abandonment in children with cancer in low-and middle-income countries (LMICs) and identify the characteristics of children and their families most disadvantaged by such abandonment. Sex-disaggregated data on treatment abandonment were collated from the available literature and a random-effects meta-analysis was conducted to compare the rates in girls with those in boys. Subgroup analyses were conducted in which st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
(218 reference statements)
0
6
0
Order By: Relevance
“…The prevalence of abandonment in South America was 18%, 12 which compares with 22% in the Asia‐Pacific region 24 . Abandonment among children with cancer is significantly high, up to 30%, in LMC 27,28 . Our study correspondingly found increased TxRA associated with the Philippines (LMIC) rather than Thailand (UMIC).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The prevalence of abandonment in South America was 18%, 12 which compares with 22% in the Asia‐Pacific region 24 . Abandonment among children with cancer is significantly high, up to 30%, in LMC 27,28 . Our study correspondingly found increased TxRA associated with the Philippines (LMIC) rather than Thailand (UMIC).…”
Section: Discussionmentioning
confidence: 53%
“…24 Abandonment among children with cancer is significantly high, up to 30%, in LMC. 27,28 Our study correspondingly found increased TxRA associated with the Philippines (LMIC) rather than Thailand (UMIC). On the contrary, Singapore (HIC) had significantly less TxRA compared with Thailand.…”
Section: F I G U R Ementioning
confidence: 54%
“…Previous studies have come to various conclusions regarding sex and care abandonment. They range from finding child cancer care abandonment to be higher in LMICs, overall, with no sex bias 31 to finding female sex plays a minor role in childhood cancer treatment abandonment, but more so in LMIC than HIC 32 . Similarly, previous studies on RB have shown variable results in the significance of association between compliance and female sex.…”
Section: Discussonmentioning
confidence: 99%
“…Available data from LMIC suggest that patients with bone sarcomas are more likely to abandon therapy, with maximum TA risk just before surgery (amputation) 81,93,95 . Risk factors for TA are geographic, travel‐related, and socio‐demographic or financial factors; a significant gender bias could not be identified from available heterogeneous data 25,93,101 . Experts suggest multiple interventions to reduce TA; like using locally adapted treatment protocols, emphasizing the need for such adaptations in LMIC 93,100–102 .…”
Section: Socio‐cultural and Logistic Challengesmentioning
confidence: 99%
“…Risk factors for TA are geographic, travel‐related, and socio‐demographic or financial factors; a significant gender bias could not be identified from available heterogeneous data 25,93,101 . Experts suggest multiple interventions to reduce TA; like using locally adapted treatment protocols, emphasizing the need for such adaptations in LMIC 93,100–102 . Shorter, simpler, and outpatient‐based protocols may be more acceptable in the AYA population 46,63,78 .…”
Section: Socio‐cultural and Logistic Challengesmentioning
confidence: 99%